Associations between degree of food processing and all-cause and cause-specific mortality: a multicentre prospective cohort analysis in 9 European countriesResearch in context - Esther M. González-Gil; Michèle Matta; Fernanda Morales Berstein; Manon Cairat; Geneviève Nicolas; Jessica Blanco; Nathalie Kliemann; Renata Bertazzi Levy; Fernanda Rauber; Inarie Jacobs; Aline Al Nahas; Emine Koc Cakmak; et al. (The Lancet Regional Health. Europe)
Summary: Background: Ultra-processed food (UPF) consumption has been linked with higher risk of mortality. This multi-centre study investigated associations between food intake by degree of processing, using the Nova classification, and all-cause and cause-specific mortality. Methods: This study analyzed data from the European Prospective Investigation into Cancer and Nutrition. All-cause mortality and cause-specific mortality due to cancer, circulatory diseases, digestive diseases, Parkinson’s disease, and Alzheimer’s disease served as endpoints. Hazard ratios (HRs) and 95% CIs were estimated using multivariable Cox proportional hazards regression models. Substitution analyses were also performed. Findings: Overall, 428,728 (71.7% female) participants were included in the analysis and 40,016 deaths were documented after 15.9 years of follow-up. UPFs (in percentage grams per day [g/d]) were positively associated with all-cause mortality (HRs per 1-SD: 1.04; 95% CI: 1.02,1.05), as well as mortality from circulatory diseases (1.09; 95% CI: 1.07,1.12), cerebrovascular disease (1.11; 95% CI: 1.05,1.17), ischemic heart disease (1.10; 95% CI: 1.06,1.15), digestive diseases (1.12; 95% CI: 1.05,1.20), and Parkinson’s disease (1.23; 95% CI: 1.06,1.42). No associations were found between UPFs and mortality from cancer or Alzheimer’s disease. Replacing processed and UPFs with unprocessed/minimally processed foods was associated with lower mortality risk. Interpretation: In this pan-European analysis, higher UPF consumption was associated with greater mortality from circulatory diseases, digestive diseases, and Parkinson’s disease. The results support growing evidence that higher consumption of UPFs and lower consumption of unprocessed foods may have a negative impact on health. Funding: l’Institut National du Cancer, and World Cancer Research Fund International.